The importance of the continuous professional development of educators for the improvement of the quality of the educational work - Christos Pappas (International Journal of Educational Excellence and Innovation, 2025)
The professional development of teachers is necessary not only for themselves and their personal development but also for the upgrading of the educational process, something that also benefits the students. This period is important because it is the first time that the teacher is confronted with the real working conditions that he will face for many years. But these first years are considered crucial for the attitude he will maintain both towards his profession and his professional development. This is also the topic that will be addressed in this paper. That is, how the newly appointed teachers are received and how this may affect their professional development.